Dental Anomalies Associated with Craniometaphyseal Dysplasia. (June 2014) - Chen, I.-P.; Tadinada, A.; Dutra, E.H.; Utreja, A.; Uribe, F.; Reichenberger, E.J.
Craniometaphyseal dysplasia (CMD) is a rare genetic disorder encompassing hyperostosis of craniofacial bones and metaphyseal widening of tubular bones. Dental abnormalities are features of CMD that have been little discussed in the literature. We performed dentofacial examination of patients with CMD and evaluated consequences of orthodontic movement in a mouse model carrying a CMD knock-in (KI) mutation (Phe377del) in the Ank gene. All patients have a history of delayed eruption of permanent teeth. Analysis of data obtained by cone-beam computed tomography showed significant bucco-lingual expansion of jawbones, more pronounced in mandibles than in maxillae. There was no measurable increase in bone density compared with that in unaffected individuals. Orthodontic cephalometric analysis showed that patients with CMD tend to have a short anterior cranial base, short upper facial height, and short maxillary length. Microcomputed tomography (micro-CT) analysis in homozygous Ank KI/KI mice, a model for CMD, showed that molars can be moved by orthodontic force without ankylosis, however, at a slower rate compared with those in wild-type Ank +/+ mice ( p < .05). Histological analysis of molars in Ank KI/KI mice revealed decreased numbers of TRAP + osteoclasts on the bone surface of pressure sides. Based on these findings, recommendations for the dental treatment of patients with CMD are provided.